2004
DOI: 10.1182/blood-2003-11-3775
|View full text |Cite
|
Sign up to set email alerts
|

Single-agent CEP-701, a novel FLT3 inhibitor, shows biologic and clinical activity in patients with relapsed or refractory acute myeloid leukemia

Abstract: Activating mutations of FMS-like tyrosine kinase 3 (FLT3) are present in approximately 30% of patients with de novo acute myeloid leukemia (AML) and are associated with lower cure rates from standard chemotherapy-based treatment. Target

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
462
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 583 publications
(472 citation statements)
references
References 33 publications
6
462
0
4
Order By: Relevance
“…There are no reports of significant cardiotoxicity in phase I-II trials of lestaurtinib in patients with acute myeloid leukaemia and activating FLT3 mutations 88 , but prospective monitoring of cardiac function has not been carried out.…”
Section: Sorafenibmentioning
confidence: 99%
“…There are no reports of significant cardiotoxicity in phase I-II trials of lestaurtinib in patients with acute myeloid leukaemia and activating FLT3 mutations 88 , but prospective monitoring of cardiac function has not been carried out.…”
Section: Sorafenibmentioning
confidence: 99%
“…2 It was shown that FLT3 inhibitors were only marginally effective in unselected AML, whereas responses were more frequently observed in patients harboring mutant FLT3. [8][9][10] For example, in the first phase I trial, testing the FLT3 inhibitor sorafenib (Nexavar, formerly BAY 43-9006) in AML only FLT3-ITD-positive (FLT3-ITD), but not FLT3-ITD-negative AML patients responded. 11 Three subsequent phase I studies underscored this evidence by demonstrating consistent activity of sorafenib in relapsed and refractory FLT3-ITD AML, while primary resistance was frequently seen in AML expressing the wild-type form of FLT3.…”
Section: Introductionmentioning
confidence: 99%
“…Relapsed/refractory AML patients showed transient clinical responses to CEP-701 in early clinical trials (Smith et al, 2004). Transient clinical responses were also observed in a Phase II trial for older AML patients not eligible for intensive chemotherapy (Knapper et al, 2006).…”
Section: Kinase Inhibitors Under Clinical Investigation For Mutant Flmentioning
confidence: 97%